Revitalizing the original game of Semarang Regency Serok Mancung - Danti Putri Subagyo; Soegiyanto Soegiyanto; Fajar Awang Irawan (Universitas Sriwijaya, 2022)
The game of Serok Mancung is an original game of Semarang Regency which has the characteristic of coconut tree midrib. This study aims to find out how the traditional game activists of Semarang Regency in revitalizing the game of Serok Mancung. This study uses qualitative methods, the data obtained through observation, interviews, and documentation. Analysis of the data in this study using Miles Hubermen, the respondents in this study were KPOTI administrators in Semarang Regency, traditional game activists, and traditional game elders in Semarang Regency. The results showed that KPOTI activists and administrators chose socialization as a form of effort to improve people's games and sports to be carried out every week. In addition, to develop this game, set tools and rules with early childhood as the target. The conclusions and suggestions in this study are that the socialization carried out by traditional game activists in terms of revitalization is said to be successful in several areas such as the districts of East Ungaran, West Ungaran, and Bergas. But so far there has been no support and appreciation from the local government regarding this revitalization.